2021
DOI: 10.3390/foods10112776
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Semi-Refined Iota Carrageenan/SiO2-ZnO Bionanocomposite Film with the Addition of Cassava Starch for Application on Minced Chicken Meat Packaging

Abstract: In the current study, film based on semi-refined ι-carrageenan/cassava starch (SRiC/CS) incorporated with SiO2-ZnO nanoparticles was fabricated and characterized to deal with serious environmental problems resulting from plastic packaging materials. This study aimed to evaluate film properties with the variation of SRiC/CS proportions of bionanocomposite films for application to minced chicken meat packaging. Increasing CS portion contributed to increased transparency, reduced surface roughness, and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
(82 reference statements)
2
6
0
2
Order By: Relevance
“…However, the inhibition zone of the SRκC−NP film at various CS concentrations exhibited antimicrobial activity against both bacteria E. coli and S. aureus . This is in agreement with previous studies that found that antimicrobial activity is increased by incorporating ZnO NPs as a filler into the film matrix [ 5 , 30 , 49 ]. In addition, a previous study showed that the antimicrobial activity of starch-based film with an antimicrobial agent contributed to extending the shelf life of meat packaging.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, the inhibition zone of the SRκC−NP film at various CS concentrations exhibited antimicrobial activity against both bacteria E. coli and S. aureus . This is in agreement with previous studies that found that antimicrobial activity is increased by incorporating ZnO NPs as a filler into the film matrix [ 5 , 30 , 49 ]. In addition, a previous study showed that the antimicrobial activity of starch-based film with an antimicrobial agent contributed to extending the shelf life of meat packaging.…”
Section: Resultssupporting
confidence: 93%
“…It was found that the incorporation of ZnO−SiO 2 NPs and CS in the matrix reduces the density of the SRκC film packaging. A similar trend was reported by Praseptiangga et al [ 49 ]. However, the obtained CS:SRκC 1:3 film packaging was the most transparent among the primary goals of this study by incorporation of CS.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A aplicação de filmes e revestimentos comestíveis apresentam atividades benéficas a cárneos, uma vez que apresentaram alternativas à conservação e manutenção dos nutrientes (Xavier et al, 2021). Carnes e peixes são alimentos perecíveis suscetíveis a rápida deterioração, assim filmes e revestimentos ativos com adição de óleos essenciais, e nanocomponentes reforçam o armazenamento prolongando a vida útil (Umaraw et al, 2020;Praseptiangga, et al, 2021). Essa abordagem atinge a perda de umidade e restringe a proliferação de microrganismos, bem como retarda a oxidação de nutrientes (Vital et al, 2018).…”
Section: Aplicações De Filmes E Revestimentos Comestíveisunclassified
“…Além disso, os aditivos podem restringir a oxidação lipídica evitando luz, oxigênio, principal processo de degradação desses alimentos (Ferreira et al, 2022;Cazón, et al, 2018). Esforços para aperfeiçoar as propriedades fisiológicas e funcionais de filmes e revestimentos comestíveis, são necessários para o setor comercial de carnes e produtos cárneos (Praseptiangga, et al, 2021).…”
Section: Aplicações De Filmes E Revestimentos Comestíveisunclassified